2000
DOI: 10.1083/jcb.148.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Requirements of Kettin, a Giant Muscle Protein Highly Conserved in Overall Structure in Evolution, for Normal Muscle Function, Viability, and Flight Activity of Drosophila

Abstract: Kettin is a giant muscle protein originally identified in insect flight muscle Z-discs. Here, we determined the entire nucleotide sequence of Drosophila melanogaster kettin, deduced the amino acid sequence of its protein product (540 kD) along with that of the Caenorhabditis elegans counterpart, and found that the overall primary structure of Kettin has been highly conserved in evolution. The main body of Drosophila Kettin consists of 35 immunoglobulin C2 domains separated by spacers. The central two thirds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 45 publications
(117 reference statements)
4
69
0
2
Order By: Relevance
“…Importantly, recent molecular genetic studies have shown that kettin is a splice variant of connectin/titin in Drosophila (Machado and Andrew, 2000;Zhang et al, 2000) and crayfish (Fukuzawa et al, 2001). Therefore, the previously reported phenotype of the Drosophila kettin mutants (Hakeda et al, 2000) may be partly due to a defect in the D-titin gene.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Importantly, recent molecular genetic studies have shown that kettin is a splice variant of connectin/titin in Drosophila (Machado and Andrew, 2000;Zhang et al, 2000) and crayfish (Fukuzawa et al, 2001). Therefore, the previously reported phenotype of the Drosophila kettin mutants (Hakeda et al, 2000) may be partly due to a defect in the D-titin gene.…”
Section: Introductionmentioning
confidence: 80%
“…Importantly, recent molecular genetic studies have shown that kettin is a splice variant of connectin/titin in Drosophila (Machado and Andrew, 2000;Zhang et al, 2000) and crayfish (Fukuzawa et al, 2001). Therefore, the previously reported phenotype of the Drosophila kettin mutants (Hakeda et al, 2000) may be partly due to a defect in the D-titin gene.Based on sequence homology, a gene coding for a kettinlike protein has been found in the nematode Caenorhabditis elegans (Hakeda et al, 2000;Kolmerer et al, 2000). Transcripts of this gene are expressed in various muscle cells, and a Abbreviations used: GST, glutathione S-transferase; Ig, immunoglobulin-like; RNAi, RNA interference.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The elastic filaments projectin and kettin (45) probably supply the radial force for lattice compression and if they bind tangentially to the end of the thick filament could also supply the necessary torque for myosin filament twist. This could explain the loss of flight in heterozygous kettin mutants in Drosophila (46).…”
Section: Discussionmentioning
confidence: 99%
“…During Drosophila embryogenesis trh is expressed in a cell population that migrates from the ventral ectoderm dorsally to become either glands (corpora cardiaca, prothoracic gland) in anterior segments, or tracheae in segments T2 through A8 (25,26). Also absent from T1 EW (Table S2) was a wing-specific isoform of salimus (sls), a gene involved in muscle development and attachment (27)(28)(29) that in Drosophila is coexpressed with trh in ventral-origin cells. Another tracheal morphogenesis gene, forked (f) (30), involved in formation of mechanosensory wing bristles (31), was among the wing-specific genes missing from T1 EW.…”
Section: Insights About Wing Origins and Functionalization From T1 Ecmentioning
confidence: 99%